Military Technical Cooperation for Development – The Brazilian Perspective of Interaction for The 21st Century (Revista da EGN, 2023)
Cooperation and development are common themes of Brazilianforeign policy. Brazil has participated in the evolution ofinternational cooperation for development since the beginning,for many years as a recipient country. Recently, Brazil has becomeinterested in being an international protagonist in the area ofdevelopment and cooperation. Since 1999, with the creation of theMinistry of Defense, it has been possible to think about unifiedmilitary technical cooperation (MTC). In this Brazilian outlook forinteraction in the 21st century, horizontal MTC stand out, withAfrica being an area of attention. In this paper, we analyze aspectsof Brazilian MTC with the Community of Portuguese LanguageSpeaking Countries (CPLP). We consider the possibility thatMTC can be presented as an element of Brazilian paradiplomacyfor development. Unlike the Organization for the Cooperationand Economic Development (OECD), Brazil includes MTC asan element of development cooperation, believing that securityand defense are issues directly related to development. Therecent stage of the MTC of Brazil with CPLP states has resultedin more coherent defense, security and development policies linkedto Brazil’s interests. Brazil created the Brazilian Cooperation Agency(ABC). However, many of the MTC projects carried out by Brazilianarmed forces with other countries are performed outside the Agency.Therefore, we analyze MTC through projects of the ABC, Ministry ofDefense and the armed forces.